I want you!: An experiment studying the selection effect when assigning distributive power - Jordi Brandts; Werner Güth; Andreas Stiehler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2002)
We study whether selection affects motivation. In our experiment subjects first answer a personality questionnaire. They then play a 3-person game. One of the three players decides between an outside option assigning him a positive amount, but leaving the two others empty-handed and allowing one of the other two players to distribute a pie. Treatments differ in the procedure by which distributive power is assigned: to a randomly determined or to a knowingly selected partner. Before making her decision the selecting player could consult the personality questionnaire of the other two players. Results show that knowingly selected players keep less for themselves than randomly selected ones and reward the selecting player more generously.
urn:nbn:de:kobv:11-10049094
Keywords: 330